Sleep problem screening of young children by speech-language pathologists: A mixed-methods feasibility study. (July 2021) - Bonuck, Karen; Battino, Risa; Barresi, Ida; McGrath, Kathleen
Background & Aims: Poor sleep in young children imperils language learning and use. Both sleep and language problems are prevalent in early childhood. Speech-language pathologists are in a unique position to expand surveillance of sleep problems, which in turn may contribute to communication difficulties. We conducted a feasibility study of speech-language pathologist screening for behavioral sleep problems and sleep-disordered breathing symptoms at a multidisciplinary evaluation and treatment center. Methods: Speech-language pathologists administered screeners to parents of 2–6-year-olds: the Short Form-Children's Sleep Habits Questionnaire (for behavioral sleep problems) which includes an item asking if the child has a sleep problem (yes/no), and the pediatric sleep questionnaire (for sleep-disordered breathing). Speech-language pathologists participated in pre- and post-screening focus groups. Pre-screening topics included professional preparation and clinical experience regarding pediatric sleep issues. Post-screening, speech-language pathologists provided feedback about the screening experience and feasibility of incorporating such screening into practice. Results: Among 51 children, 31% (16/51) screened positive for sleep-disordered breathing, 78% for behavioral sleep problems (40/51), and 43% (12/28) per parent report. Parent-reported problems were associated with sleep-disordered breathing ( p = 0.00) but not behavioral sleep problems ( p = 0.24). During focus groups, speech-language pathologists reported no formal pediatric sleep training, high parent concern about sleep, and agreed that screening fit their professional mandate. Speech-language pathologists affirmed that the ≤15 min screenings integrated seamlessly into practice but that additional training, particularly for sleep-disordered breathing, was needed. Conclusions: The prevalence of sleep problems in 2–6-year-olds presenting to speech-language pathologists was higher than in community samples, but consistent with data from young children with developmental disabilities. Speech-language pathologists endorsed the utility and feasibility of sleep problem screening and education in their clinical practice. Implications: Integrating sleep problem screening and education into speech-language pathologist practice is feasible and could widen surveillance of both sleep problems and risk factors for developmental language disorders. Further research should include larger samples and other settings, e.g. home or school.